The Impact of a Public Speaking and Writing Skills Workshop on Student Preparation and Empowerment in International Academic Forums - Yulianita, Neni; Maryani, Anne; Wiwitan, Tresna; Rakhmatullah, Adhika Putra; Maulana, Faisal; Irvanianto, Raihan Firjatullah (Annpublisher, 2025)
Background. Speaking and writing are essential communication skills for students in academic settings and international forums, enabling them to convey ideas clearly and effectively in presentations, seminars, and scientific publications. Aim. This study aims to evaluate the effectiveness of a workshop on speaking and writing skills in enhancing students’ academic communication abilities, particularly in preparation for participation in international academic forums. Methods. Through the workshop activities carried out, the level of knowledge of participants was evaluated using a descriptive approach. The instruments used to collect data were a pre-test and a post-test. Results. The results of this training were effective in improving participants' knowledge and skills, as indicated by the effectiveness measurement. Workshop participants were involved in speaking and writing to enhance their academic achievement in international forums, which will enable them to participate in the International Conference on Communication, Management, and Humanities (ICCOMAH VI) 2025. Conclusions. Speaking and writing skills are crucial for students in academic settings, especially in international forums. These abilities support the delivery of precise ideas, enhance academic performance, and enable students to present their thoughts systematically, making them easier to understand by diverse audiences. Implementation. The workshop was conducted through interactive sessions, writing and speaking exercises, and academic forum simulations to improve participants’ communication skills gradually